A Case of Facial Partial Unilateral Lentiginosis Treated with Low-Fluence 1,064 nm Q-Switched Neodymium-Doped Yttrium Aluminum Garnet Laser - En Hyung Kim (Karger Publishers, 2017)
Partial unilateral lentiginosis (PUL) is an unusual pigmentary disorder characterized by numerous lentigines grouped within an area of normal skin. Although treatment is not necessary, many patients with facial PUL seek medical help for cosmetic reasons. There is no established standard treatment for PUL. Conventional lasers may cause postinflammatory hyperpigmentation because keratinocytes are injured during the process. Also, scarring, long downtime, and pain are important issues. A 19-year-old patient with facial PUL was successfully treated with low-fluence 1,064-nm Q-switched neodymium-doped yttrium aluminum garnet (QS Nd:YAG) laser. Although the exact mechanism by which low-fluence 1,064-nm QS Nd:YAG laser improves pigmentary lesions is unclear, the terms "subcellular selective photothermolysis" and "melanocyte apoptosis and replacement" have been proposed. If appropriate measures are taken to monitor patient response during and after the procedure, low-fluence 1,064-nm QS Nd:YAG laser may achieve good cosmetic results in the treatment of PUL with a very safe and effective profile.